Assessing the impact of agricultural research on poverty using the sustainable livelihoods framework - Adato, Michelle; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2002)
As the goals of international agricultural research move beyond increasing food production to the broader aims of reducing poverty, both agricultural research and studies of its impact become more complex. Yet examining the magnitude and mechanisms through which different types of agricultural research are able to help the poor is essential, not only to evaluate claims for continued funding of such research, but more importantly, to guide future research in ways that will make the greatest contribution to poverty reduction. This paper reports on the approach used in a multicountry study of the poverty impact of research programs under the Consultative Group on International Agricultural Research (CGIAR). The studies use an expanded understanding of poverty that goes beyond income- or consumption-based headcounts or severity measures, to consider many other factors that poor people in different contexts define as contributing to their vulnerability, poverty, and well-being. The sustainable livelihoods framework provides a common conceptual approach to examining the ways in which agricultural research and technologies fit (or sometimes do not fit) into the livelihood strategies of households or individuals with different types of assets and other resources, strategies that often involve multiple activities undertaken at different times of the year. This paper reports on the conceptual framework, methods, and findings to date of these studies. It provides an overview of the sustainable livelihoods approach, how it can be applied to agricultural research, and describes detailed methods and results from five case studies: (1) modern rice varieties in Bangladesh; (2) polyculture fishponds and vegetable gardens in Bangladesh; (3) soil fertility management practices in Kenya; (4) hybrid maize in Zimbabwe; and (5) creolized maize varieties in Mexico. This was also published as FCND Discussion Paper 128.